2020
DOI: 10.3390/microorganisms8111695
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Native Arbuscular Mycorrhizal Fungi, Rhizobia, and/or Green Compost as Alfalfa (Medicago sativa) Enhancers under Salinity

Abstract: Salinity is one of the devastating abiotic stresses that cause reductions in agricultural production. The increased salinization affects alfalfa growth, metabolism, and rhizobium capacity for symbiotic N2 fixation negatively. This study was undertaken to investigate the efficiency of green compost (C; made from green waste), arbuscular mycorrhizal fungi (M; field-sourced native consortium), and/or rhizobium (R; a salt-tolerant rhizobium strain) individually or in combination as an effective strategy to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 74 publications
(130 reference statements)
5
40
0
Order By: Relevance
“…1 ). The inhibitory effects of salt stress on shoot growth were greater than those on root growth (Table 1 ), which is consistent with Qiu et al 11 and Ben-Laouane et al 26 but not with Ait-El-Mokhtar et al 17 Salt stress had different effects on the root and shoot growth of different sweet sorghum varieties 10 . Is the varying sensitivity of the roots and stems of different plants to stress related to their particular mechanisms of coping with stress?…”
Section: Discussionsupporting
confidence: 84%
“…1 ). The inhibitory effects of salt stress on shoot growth were greater than those on root growth (Table 1 ), which is consistent with Qiu et al 11 and Ben-Laouane et al 26 but not with Ait-El-Mokhtar et al 17 Salt stress had different effects on the root and shoot growth of different sweet sorghum varieties 10 . Is the varying sensitivity of the roots and stems of different plants to stress related to their particular mechanisms of coping with stress?…”
Section: Discussionsupporting
confidence: 84%
“…However, to facilitate the widespread adoption of these technologies in agriculture, their potential and reliability need to be validated in the field to ensure that they remain affordable and more effective than the existing approaches. Previous studies demonstrated the role of AMF on drought and salt stress mitigation in alfalfa, date palm, and carob plants [ 44 , 45 , 46 ]. However, the role of native AMF in combination with vermicompost on alterations in ROS scavenging machinery, to impart tolerance against field drought stress, has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Under DS, quinoa plants inoculated with AMF accumulated higher proteins and sugar content, likely to maintain high hydration and turgor levels and to maintain the overall physiological traits [ 95 , 116 ]. In addition, the higher content of soluble proteins in inoculated and amended plants may explain the strengthening of the enzymatic antioxidant defense system under abiotic stress [ 28 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the well-documented action of phosphate-solubilizing and nitrogen-fixing microorganisms in plant P and N nutrition [ 13 , 14 ], the importance of microbial activity on plant K nutrition is less well understood. It has been shown that bacteria and mycorrhizal fungi do solubilize mineral K by various mechanisms such as production of alkaline substances including ammonia and other metabolites upon death of microbial cells and subsequent proteolysis [ 15 , 16 ]. K-solubilizing bacteria (KSB) have attracted more attention because of their ability to increase plant growth and yield [ 17 ].…”
Section: Introductionmentioning
confidence: 99%